An examination of the performance of hedge funds in South Africa - Makhubela, Romeo (My University, 2021)
This study examines the hedge fund industry's performance in South Africa from 31 March 2015 to 31 March 2020. The period under review is significant as the hedge fund industry was first regulated and monitored from 2015 onwards. The industry has been seen by critics and other stakeholders as greedy, corrupt, and charging outrageous investor fees. Since the global financial crisis of 2008 and the subsequent recession, the hedge fund industry has underperformed its respective benchmarks on average. The study seeks to analyse the hedge fund strategies' performance in South Africa against their benchmarks for a 5-year monthly period starting March 2015 to March 2020 against traditional investment products' benchmarks such as the All-Share, SWIX SA, and All bond Index. The exercise aims to establish whether investors are adequately compensated for their fees against these products' risks and returns. Another critical factor in our analysis is to determine whether or not the industry performance has been persistent. Persistency of Performance is tested using different statistical methodologies such as Cross Product Ratio (CPR) Test, Chi-Square Test, Cross-Sectional Regression (CSR) Test and, Binomial Test to understand whether skill or luck is a factor in analysing the performance of managers
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Hedge fund(s); Cross Product Ratio (CPR); UCTD; SDG-8: Decent work and economic growth